Learn all about meditation from the Himalayan mystic : a million thoughts - Swami, Om. (Delhi : Jaico Publishing House, 2017)
A Million Thoughts shows how to meditate correctly, how to practice various styles of meditation and how to become proficient in the many yogic practices that will lead to the final stage of samadhi--the ultimate spiritual self-fulfilment"--Back cover.
Keywords: Meditation -- Hindusuim